An efficient implementation of the light scattering simulation for random-oriented non-rotationally symmetric particles using invariant imbedding T-matrix method. (January 2020) - Hu, Shuai; Liu, Lei; Gao, Taichang; Zeng, Qingwei; Liu, Xichuan
Highlights: To give a more full description of the analytical algorithm to calculate the scattering parameters of the random-oriented particles with arbitrary shapes, the derivation process of this model is deduced following Mishchenko's idea in this paper. To facilitate the realization of this algorithm, an efficient implementation of the computational scheme is introduced in detail. The analytical algorithm can calculate the scattering parameters of the random-oriented particles with high accuracy and efficiency. Abstract: In atmospheric radiative transfer models, the light scattering properties of the nonspherical particles are needed to be averaged over specific orientation and size distributions to obtain the representative values. However, since the light scattering simulation processes of the typical models (such as DDA, FDTD, etc.) are closely dependent on particle's orientation, their computations should be repeated for many times to realize the orientation averaging process, which is a very time-consuming task. To solve this problem, the analytical algorithm to calculate the scattering parameters of the random-oriented particles based the Invariant Imbedding T-matrix method (IIM T-matrix method) is developed by Bi L., by which the scattering parameters of the randomly oriented particles can be calculated analytically. To give a more full description of this algorithm, the derivation process of this model is deduced following Mishchenko's idea in this paper. To facilitate the realization of this algorithm, an efficient implementation of the computational scheme is also introduced in detail. To validate the modeling accuracy of this algorithm, the results of the IIM T-matrix method are compared with those of the EBCM T-matrix method and DDASCAT for particles with different sizes and shapes. The results show that good agreement is achieved between the scattering parameters calculated by different models, where, the relative differences between the phase functions calculated by IIM and EBCM method are generally smaller than 5%, and the relative deviations of the extinction, scattering cross sections are all less than 0.5%, which indicates that the analytical algorithm can simulate the scattering parameters of the random-oriented particles with high accuracy. Compared to the traditional T-matrix method, the advantage of this algorithm is that it can be applicable to arbitrarily shaped particles.